2017
DOI: 10.18632/oncotarget.19201
|View full text |Cite
|
Sign up to set email alerts
|

Tripchlorolide induces autophagy in lung cancer cells by inhibiting the PI3K/AKT/mTOR pathway and improves cisplatin sensitivity in A549/DDP cells

Abstract: Tripchlorolide (T4) has been shown to induce A549 lung cancer cell death predominantly by activating an autophagy pathway. However, the underlying mechanism remains unclear. Herein, we demonstrated that compared with T4 treatment alone, pretreatment with wortmannin (an inhibitor of phosphatidylinositol 3-kinase), perifosine (an inhibitor of AKT) or rapamycin (an inhibitor of mTOR) combined with a subsequent T4 treatment significantly impaired the cell viability of A549 and A549/DDP lung cancer cells. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
(28 reference statements)
3
20
0
Order By: Relevance
“…Rapamycin is an inhibitor of mTOR and may activate autophagy (20,21). The present study revealed that rapamycin significantly inhibited PQ-induced EMT and the Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…Rapamycin is an inhibitor of mTOR and may activate autophagy (20,21). The present study revealed that rapamycin significantly inhibited PQ-induced EMT and the Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…Documents demonstrated that autophagy contributes to cell survival and homeostasis by removing them is folded proteins and damaged organelles as well as intracellular pathogens through the lysosomal degradation pathway [16,39]. However, autophagy is a complicated pathway and activated by variety of factors, such as exposure to anoxia, starvation, chemical agents and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16]. As the number of scientists investigating autophagy has increased, the complexity of autophagy has become increasingly dissected.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that T4 can increase the sensitivity of A549/DDP cells to cisplatin by decreasing the expression of MDR1. [15] Therefore, in this experiment, we decided to investigate the following: (1) whether AEG-1 affects the drug resistance of lung cancer cells, and (2) whether T4 can affect the expression of AEG-1 protein in lung cancer cells, and (3)whether T4 reduces cisplatin resistance by inhibiting AEG-1 gene expression in lung cancer cells. We clearly determined that AEG-1 protein is closely related to the drug resistance of lung cancer cells and found that T4 can in uence the expression of AEG-1 protein in lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%